Application of Group Investigation Learning Models and Inquiry Learning Strategies to Improve Students’ Learning Outcomes - Ifaksasily, Tania; Muskitta, Marike (RUMPHIUS, 2024)
Group investigation is a learning model focused on collaboration between teachers and students, involving task sharing, sub-theme assignments, and presentation schedules. Inquiry learning emphasizes critical and analytical thinking to solve problems or answer questions, and it can involve the use of miniature models to enhance cognitive and metacognitive skills. The aim of this study is to determine how the integration of the Group Investigation Learning Model and Inquiry Learning Strategy impacts cognitive and metacognitive learning outcomes in students at the Fourth Public Senior High School of Ambon, Maluku Province. The methods used in this research are descriptive statistics and inferential statistics. Based on the cognitive learning results of analysis covariance, the significant value is 0.001, which is less than the critical value of 0.05. This means that the research hypothesis is accepted, indicating that there is an influence of the Group Investigation model and Inquiry Strategy on the improvement of learning outcomes for students in the Eleventh Grade Natural Sciences Interest Group. Additionally, the metacognitive learning result has a significant value of 0.006, which is less than critical value, meaning that the hypotheses are accepted, indicating that Group Investigation and learning strategies have a positive influence on improving students' metacognitive learning outcomes.